THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. EGA WAYANG GARMINDO NORTH JAKARTA - Dewi Lestari (Yayasan Education and Social Center, 2023)
The purpose of this study was to determine how much influence motivation and work environment have on employee performance at PT. Ega Wayang Garmindo, North Jakarta, either partially or simultaneously. The research method uses a quantitative research method with a descriptive quantitative approach. The sample used in this study is a saturated sample, namely using the entire population of 57 people as a sample. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of the research show that there is a positive influence between employee motivation and performance partially. Where is the simple linear regression equation Y = 8.039 + 0.789 X1 means it has a positive effect, the correlation test r = 0.760 is included in the strong category, the coefficient of determination is 57.8% and the remaining 42.2% is influenced by other factors, the t test is tcount 8.684 > ttable 1.673 then Ha1 is accepted and Ho1 is rejected. The results showed that there was a positive influence between the work environment and employee performance partially. Where is the simple linear regression equation Y = 7.853 + 0.787 X2 means that it has a positive effect, the correlation test r = 0.861 is included in the very strong category, the coefficient of determination is 74.2% and the remaining 25.8% is influenced by other factors, the t test is tcount 12.578> ttable 1.673 then Ha2 is accepted and Ho2 is rejected. The results showed that there was a positive influence between the variables of motivation and work environment on employee performance simultaneously, where the multiple regression equation Y = 4.699 + 0.242 X1 + 0.622 X2 means a positive effect, multiple correlation test r = 0.874 is included in the very strong category, the coefficient of determination of 76.4% and the remaining 23.6% which is influenced by other factors, the f test of fcount 87.374 > ftable 3.168 means that it can be concluded that the variables of motivation and work environment have a significant effect on employee performance